Cladieunicellins R and S, new eunicellins from the Formosan octocoral Cladiella tuberculosa. Issue 37 (14th September 2016) - Peng, Kai-Yu; Chen, Nan-Fu; Chen, Zhi-Cheng; Tsui, Kuan-Hao; Wen, Zhi-Hong; Su, Yin-Di; Chang, Yu-Chia; Chen, Yu-Hsin; Lu, Mei-Chin; Fang, Lee-Shing; Chen, Jih-Jung; Wu, Tung-Ying; et al.
Graphical abstract: Highlights: Two novel eunicellins, cladieunicellin R and S, are isolated. Cladieunicellin R was proven to be the first 2, 6-hemiketal eunicellin. Cladieunicellin S exhibited moderate cytotoxicity toward the human leukemia MOLT-4, K562, and SUP-T1 cells. Abstract: Two new eunicellin-type diterpenoids, cladieunicellins R (1 ) and S (2 ), were isolated from the octocoral Cladiella tuberculosa and their structures were elucidated by spectroscopic methods. Eunicellin1 was proven to be the first 2, 6-hemiketal eunicellin and2 was found to exhibit moderate cytotoxicity toward the MOLT-4, K562, and SUP-T1 cells.